Non-Celiac Gluten Sensitivity in patients with severe abdominal pain and bloating: The accuracy of ALCAT 5. (December 2018) - Di Stefano, Michele; Pesatori, Eugenia Vittoria; Manfredi, Giulia Francesca; De Amici, Mara; Grandi, Giacomo; Gabriele, Alessandro; Iozzi, Davide; Di Fede, Giuseppe
Summary: Background and aims: Non-Celiac Gluten Sensitivity (NCGS) is a recently proposed clinical condition causing both intestinal and extra-intestinal symptoms, without gastrointestinal lesions, which improve on avoiding gluten intake, in the absence of celiac disease and wheat allergy. The prevalence of this condition is still a matter of debate, in part due to the very recent introduction of an accepted diagnostic test, a double-blind, placebo controlled gluten challenge. However, this is a lengthy and cumbersome procedure, theoretically burdened by a significant reduction of patient compliance. ALCAT 5 is an automated in vitro test evaluating the toxic effect of gluten on neutrophils by the exposure of these cells to a gluten-containing extract of gluten-containing cereals. The test is very simple to perform, the results are rapidly obtained, and might represent, if sufficiently accurate, a promising alternative to diagnose gluten intolerance. The aim of this study was the comparison of ALCAT 5 results with those of a double-blind, placebo-controlled, gluten challenge, in a group of patients with clinically-suspected NCGS. Methods: Twenty-five patients (M/F 3/22, mean age 32 ± 4 yrs) with severe functional abdominal pain and bloating, who had previously undergone the ALCAT 5 test, were enrolled. All the subjects reported their symptoms on a gluten-containing diet and considered gluten the causal agent. Following the Salerno Experts' Criteria, they underwent a double-blind, placebo controlled trial with gluten vs placebo. A mean value during gluten ingestion >30% of the value during placebo was considered as indicative of gluten sensitivity. Results: After blinded administration of gluten, 13 out of 25 (52%) patients showed an increase in the severity of abdominal pain, and 11 out of 25 (44%) showed an increase in the severity of abdominal bloating. Considering these two symptoms together, in 16 patients out of 25 (64%), blinded gluten administration induced an increase of abdominal pain and/or bloating. The ALCAT 5 test proved to be positive in 20 and negative in 5 patients. In sixteen patients out of 25 the result of ALCAT 5 agreed with the double-blind trial (64%). In particular, both tests were positive in 14 patients and negative in 2. Conclusions: In this subgroup of patients, ALCAT 5 could be used to support the clinical suspicion of the presence of NCGS and to address these patients to a blinded gluten challenge.